Adolescents' role in family decision-making for services in India. Issue 4 (21st November 2016) - Ashraf, Maria; Khan, Kaleem Mohammad
Abstract : Purpose: The purpose of this paper is to understand the involvement of adolescents in family vacation and dining out on the basis of the type of family. Also, the purpose of this paper is to refine the Scanzoni's sex role orientation scale (SSRS) in the Indian context. Design/methodology/approach: Data were collected using self-administered questionnaires from adolescents in Delhi and Uttar Pradesh (states in India). The response rate is 44.88 per cent. Sex role orientation was measured using the Scanzoni's SSRS. Findings: There is a decline in the involvement of adolescents through the major decision-making stages for both the services, family vacation and dining out. There is no significant difference in the involvement of adolescents in dual-income and single-income families for a vacation and dining out, except that the children from dual-income families are more involved in destination selection for a vacation. Also, the adolescents in modern families are significantly involved in the sub-decision stages, spending and selection of travel agent. Practical implications: The marketers should advertise the vacation destinations to adolescent children in dual-earning families. Also, the travel agencies should design their promotion strategies so as to appeal to the adolescent children with modern attitudes. While catering to the needs of a family, travel agencies must present their services in a way that appeals to adolescents in modern families. Also, this aspect must be taken care of in all the pricing strategies and promotions for the modern families. Originality/value: Despite the large number of studies in various Western countries in this area, few studies investigate adolescent influence in family decision-making in India. The present study takes into account the type of family, single income or dual income (on the basis of the employment of parents) and traditional or modern (on the basis of gender role orientation).